2013
DOI: 10.1097/wco.0b013e32835ee5b8
|View full text |Cite
|
Sign up to set email alerts
|

Connectomics and epilepsy

Abstract: Purpose of review Tremendous advances have occurred in recent years in elucidating basic mechanisms of epilepsy at the level of ion channels and neurotransmitters. Epilepsy, however, is ultimately a disease of functionally and/or structurally aberrant connections between neurons and groups of neurons at the systems level. Recent advances in neuroimaging and electrophysiology now make it possible to investigate structural and functional connectivity of the entire brain, and these techniques are currently being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 53 publications
7
194
1
3
Order By: Relevance
“…Most epilepsies develop not from alterations of a single target, but rather from complex alterations that result in an epileptic network in the brain [3,45,46]. The only existing cure of epilepsy in many patients is resective surgery in which the regional epileptic network, or part of this network, is removed [47].…”
Section: Concept Of Network Pharmacologymentioning
confidence: 99%
“…Most epilepsies develop not from alterations of a single target, but rather from complex alterations that result in an epileptic network in the brain [3,45,46]. The only existing cure of epilepsy in many patients is resective surgery in which the regional epileptic network, or part of this network, is removed [47].…”
Section: Concept Of Network Pharmacologymentioning
confidence: 99%
“…Vladmir Komárek, M. Kynčl, J. Šanda, M. Vránová, R. Vydrová-Recent research showed the importance of language-associated pathways during brain development as well as in the presurgical assessment of children with refractory epilepsy, namely with epileptogenic zone in language-related regions [153][154][155][156]. Currently, language studies agree on the concept of two interacting pathways connecting the language-relevant regions in the temporal and the frontal cortices.…”
Section: Mapping Language and Epilepsy Network In The Developing Brainmentioning
confidence: 99%
“…In post-SE rat models of TLE an acute increase in ADC, beginning as early as 3 mins post-SE [39], has been reported [17,40]. However, this is a dynamic and structurallydependent response, with reports of acute decreases in ADC post-SE [17,[39][40][41][42], a return to baseline by 1 week, and increased ADC at chronic time-points [39].…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
“…However, this is a dynamic and structurallydependent response, with reports of acute decreases in ADC post-SE [17,[39][40][41][42], a return to baseline by 1 week, and increased ADC at chronic time-points [39]. ADC increases may be related to vasogenic edema or increased metabolic activity [17,39,43,44], whereas the acute ADC decreases are associated with cytotoxic edema and neuronal loss [39,43,44].…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%